1999
DOI: 10.1007/s001140050676
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Lichens and Their Metabolites

Abstract: Lichens, symbiontic organisms of fungi and algae, synthesize numerous metabolites, the "lichen substances," which comprise aliphatic, cycloaliphatic, aromatic, and terpenic compounds. Lichens and their metabolites have a manifold biological activity: antiviral, antibiotic, antitumor, allergenic, plant growth inhibitory, antiherbivore, and enzyme inhibitory. Usnic acid, a very active lichen substance is used in pharmaceutical preparations. Large amounts of Pseudevernia furfuracea and Evernia prunastri are proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
238
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(253 citation statements)
references
References 69 publications
4
238
1
10
Order By: Relevance
“…Cladonia, Ramalina, Usnea and others. The biological activities of usnic acid such as antiviral (Scirpa et al 1999), antifungal (Lauterwein et al 1995, Lawrey 1995, Cocchietto et al 2002, antiprotozoal (Fournet et al 1997), antiproliferative, antiherbivoral (Huneck 1999), analgesic (Vijayakumar et al 2000), hepatotoxic (Pramyothin et al 2004) have been reviewed by Ingolfsdottir (2002). Rankovic et al (2007) determined that usnic asid has the strongest antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cladonia, Ramalina, Usnea and others. The biological activities of usnic acid such as antiviral (Scirpa et al 1999), antifungal (Lauterwein et al 1995, Lawrey 1995, Cocchietto et al 2002, antiprotozoal (Fournet et al 1997), antiproliferative, antiherbivoral (Huneck 1999), analgesic (Vijayakumar et al 2000), hepatotoxic (Pramyothin et al 2004) have been reviewed by Ingolfsdottir (2002). Rankovic et al (2007) determined that usnic asid has the strongest antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are about 20,000 species of them around the world, and even they make 8% of the terrestrial ecosystems, their biological activity and biological components are not distinguished very much (Toma et al, 2001). Various biological activities of some lichens and their components are known, such as antiviral, anti-tumor, anti-inflammatory, analgetic, antipyretic, anti-proliferative, antiprotozoal (Lawrey, 1986;Halama et al, 2004;Huneck, 1999). Besides, many species are used for human nutrition, animal nutrition, for getting colors, perfumes, alcohol and in the medicine industry (Kirmizigul et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many species are used for human nutrition, animal nutrition, for getting colors, perfumes, alcohol and in the medicine industry (Kirmizigul et al, 2003). Lichens have also, for hundreds of years, been used in many European countries as a cure for stomach diseases, diabetes, cough, pulmonary tuberculosis, wounds curing, dermatological diseases (Baytop, 1999;Huneck, 1999). The usage of some lichens in the traditional medicine for many years was later justified by numerous researches which proved their antimicrobal activity (Cansaran et al, 2006;Choudhary et al, 2005;Gulluce et al, 2006;Rankovic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, lichenized fungi make up almost half of all known ascomycetes (Kirk et al, 2001) and are known to produce over 800 secondary metabolites, most of which are unique to lichenized fungi. Many of these compounds have bioactive properties (Huneck, 1999) and some studies have shown or suggested that secondary metabolite production is influenced by changes in culture conditions, which might be regarded as environmental changes. Intense investigation of the changes in production of these unique bioactive secondary metabolites from lichen fungi have been hampered by problems associated with isolating and growing cultures of lichen fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews and inventories of lichen metabolites are summarized by Culberson C. F. & Elix (1989), Elix & Stocker-Worgotter (2008) ;Culberson C. F. (1969) ;Culberson C. F. (1970) ;Culberson C. F., et al (1977b); Stocker-Worgotter (2008); and a recent classification of lichen substances (Culberson C. F. & Elix, 1989). The adaptive significance of secondary metabolites produced by lichen fungi has been speculated (Lawrey 1977) and numerous functional studies (reviewed in Huneck, 1999), but few studies have linked adaptation of lichen substances with environmental change. This chapter provides a synopsis of secondary metabolite production in fungi with a focus on lichenized fungi.…”
Section: Introductionmentioning
confidence: 99%